Forest restoration treatments have subtle long‐term effects on soil C and N cycling in mixed conifer forests. Issue 5 (5th July 2016) - Ganzlin, Peter W.; Gundale, Michael J.; Becknell, Rachel E.; Cleveland, Cory C.
Abstract: Decades of fire suppression following extensive timber harvesting have left much of the forest in the intermountain western United States exceedingly dense, and forest restoration techniques (i.e., thinning and prescribed fire) are increasingly being used in an attempt to mitigate the effects of severe wildfire, to enhance tree growth and regeneration, and to stimulate soil nutrient cycling. While many of the short‐term effects of forest restoration have been established, the long‐term effects on soil biogeochemical and ecosystem processes are largely unknown. We assessed the effects of commonly used forest restoration treatments (thinning, burning, and thinning + burning) on nutrient cycling and other ecosystem processes 11 yr after restoration treatments were implemented in a ponderosa pine ( Pinus ponderosa var. scopulorum )/Douglas fir ( Pseudotsuga menziesii var. glauca ) forest at the Lubrecht Fire and Fire Surrogates Study (FFS) site in western Montana, USA. Despite short‐term (<3 yr) increases in soil inorganic nitrogen (N) pools and N cycling rates following prescribed fire, long‐term soil N pools and N mineralization rates showed only subtle differences from untreated control plots. Similarly, despite a persistent positive correlation between fuels consumed in prescribed burns and several metrics of N cycling, variability in inorganic N pools decreased significantly since treatments were implemented, indicating a decline in N spatial heterogeneity through time. However, rates of net nitrification remain significantly higher in a thin + burn treatment relative to other treatments. Short‐term declines in forest floor carbon (C) pools have persisted in the thin + burn treatment, but there were no significant long‐term differences among treatments in extractable soil phosphorus (P). Finally, despite some short‐term differences, long‐term foliar nutrient concentrations, litter decomposition rates, and rates of free‐living N fixation in the experimental plots were not different from control plots, suggesting nutrient cycles and ecosystem processes in temperate coniferous forests are resilient to disturbance following long periods of fire suppression. Overall, this study provides forest managers and policymakers valuable information showing that the effects of these commonly used restoration prescriptions on soil nutrient cycling are ephemeral and that use of repeated treatments (i.e., frequent fire) will be necessary to ensure continued restoration success.